2015
DOI: 10.1017/s0031182015000803
|View full text |Cite
|
Sign up to set email alerts
|

Immunophilin–protein interactions inPlasmodium falciparum

Abstract: SUMMARY 24Immunophilins comprise two protein families, cyclophilins (CYPs) and FK506-binding 47• PfCYP19B interacts specifically with PfHsp70. 48• Cyclophilin ligands disrupt transport of RAP1 in cultured parasites. 49

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The compounds chosen included CsA, the standard antimalarial drugs artemisinin and chloroquine, the Hsp90 inhibitor geldanamycin and the Hsp70 inhibitor pifithrin- μ . We choose the last two because both heat-shock proteins interact with PfFKBP35 (Kumar et al 2005; Leneghan & Bell, 2015) and there was a possibility that this might lead to interactions of Hsp90 or Hsp70 inhibitors with FK506 and/or Rap. Pifithrin- μ had not previously been tested on Plasmodium but we found it to be antimalarial in culture with an IC 50 of 15 µ m .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds chosen included CsA, the standard antimalarial drugs artemisinin and chloroquine, the Hsp90 inhibitor geldanamycin and the Hsp70 inhibitor pifithrin- μ . We choose the last two because both heat-shock proteins interact with PfFKBP35 (Kumar et al 2005; Leneghan & Bell, 2015) and there was a possibility that this might lead to interactions of Hsp90 or Hsp70 inhibitors with FK506 and/or Rap. Pifithrin- μ had not previously been tested on Plasmodium but we found it to be antimalarial in culture with an IC 50 of 15 µ m .…”
Section: Resultsmentioning
confidence: 99%
“…The function of PfFKBP35 can be guessed at based on data from FKBPs of other organisms (Bell et al 2006) – we expect it to be involved in folding, transport and/or regulation of other proteins and perhaps in the response to stresses such as the temperature shocks encountered on transfer between hosts (Acharya et al 2007). Its interacting partner proteins are now known to include heat-shock proteins and histones (Leneghan & Bell, 2015) but the physiological/biochemical consequences of these molecular interactions have not yet been extensively investigated. In this paper, we have shown that the pharmacodynamic actions of two PfFKBP35 ligands, FK506 and Rap, were essentially indistinguishable.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclophilins belong to the immunophilin class of proteins 18 and some members of this family have been associated with parasitic diseases. Human malaria parasite P. falciparum encodes 13 immunophilins or immunophilin-like proteins; however, their exact functions are still unknown 19 21 .…”
Section: Introductionmentioning
confidence: 99%
“…PF3D7_0604500 encodes a protein containing a GYF domain, which recognizes the proline-rich sequence. It was found to interact with PfCYP19A, a peptidyl-prolyl cistrans isomerase in P. falciparum [321].…”
Section: Common Interacting Partners Of Caf1 and Not4mentioning
confidence: 99%